2007
DOI: 10.1103/physrevb.76.134109
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical stability of molybdenum nitrides: A first-principles study

Abstract: We report theoretical calculations based on ab initio total-energy calculations within the density functional theory to determine the structural, elastic, and electronic properties for several MoN phases. Among the five crystallographic structures that have been investigated, the hexagonal phases have been found to be more stable than the cubic ones. The calculated equilibrium structural parameters are in agreement with the available experiment results. It was found that ␦ 3 -MoN has the highest bulk modulus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
6
43
1
1
Order By: Relevance
“…The analysis of the density of states of δ1-MoN and δ3-MoN phases show that the high values of bulk modulus result from the covalent character of the bonding due to the strong hybridization between N and Mo states [38]. The authors have also observed a strong directional charge redistribution from Mo to N atoms, which reflects the electronegative nature of N atoms and adds an ionic contribution to the metallic character of compounds.…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasesmentioning
confidence: 77%
See 1 more Smart Citation
“…The analysis of the density of states of δ1-MoN and δ3-MoN phases show that the high values of bulk modulus result from the covalent character of the bonding due to the strong hybridization between N and Mo states [38]. The authors have also observed a strong directional charge redistribution from Mo to N atoms, which reflects the electronegative nature of N atoms and adds an ionic contribution to the metallic character of compounds.…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasesmentioning
confidence: 77%
“…Kanoun et al [38] and more recently Zhao et al [39] have also calculated the bulk modulus corresponding to the stoichiometric MoN phase of hexagonal structure by use of the density functional theory ( Table 3). The analysis of the density of states of δ1-MoN and δ3-MoN phases show that the high values of bulk modulus result from the covalent character of the bonding due to the strong hybridization between N and Mo states [38].…”
Section: Stoichiometric δ-Mon and Cubic Mon Phasesmentioning
confidence: 99%
“…Our results fit the observations that MoN is mechanically unstable in the vacancy-free structures based on zincblende-ZnS, NaCl, or CsCl. 18,39,40 This low-energy cubic crystal structure for 1:1 stoichiometry, i.e., the NbO-type, is still by about 0.05 eV/at less favorable than the vacancy-free NiAs-based Based on our results that the ordering of N-vacancies within the cubic c-MoN x -based structure is energetically preferred for x between 0.6 and 0.7 (hence, E f is more negative for c 0 -MoN x than for c-MoN x , Fig. 1), we studied additional structures based on the M 3 X 2 -type (i.e., MoN 0.67 ) as given in Ref.…”
Section: A Computational Resultsmentioning
confidence: 99%
“…The recent chemical syntheses of novel nitride compounds [23][24][25][26] have stimulated extensive studies on transition metal nitrides to search for less compressible materials [27][28][29]. Recent first-principles calculations on OsN [28] and MoN [29] revealed that their hexagonal phases (WC structure) have higher bulk modulus than the cubic phases (NaCl structure) and that these nitrides with hexagonal phases are low-compressibility materials.…”
Section: Introductionmentioning
confidence: 99%